The effectiveness of Counseling Social Cognitive With Sociodrama Techniques to enhance other people's Fun Characters through Lesson Study - Ni Ketut Hefi Teaningsih; Kadek Suranata; Kadek Suranata (RedwhitePress)
This study aims to • determine the effectiveness of counseling social cognitive techniques for improving sociodramas fun characters of others through the lesson study. Type of quasi-experimental research, with a pretest-posttest control group design. This study population, 56 students and this study're the sample of 20 students, Collecting data using questionnaires breaking every character win the others with 30 items. The results of the data analysis tcount 37.14 > ttable 2.09 so that ho refused and accepted ha. So there is a significant difference. It can be concluded that the effectiveness of social cognitive counseling with effective techniques to improve the character sociodramas pleases others.